(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The intricate relationship between language and philosophy has long been a subject of scholarly interest. Philosophical terms often encapsulate profound and abstract ideas, necessitating precise and effective linguistic expressions. This thesis focuses on the morphological methods by which these terms are formed in the English language. Morphology, the study of the structure and formation of words, provides valuable insights into how complex philosophical notions are constructed and conveyed through language. By analyzing the morphological processes such as affixation, compounding, and derivation, this research aims to uncover the underlying linguistic mechanisms that facilitate the articulation of philosophical ideas. Understanding these methods is crucial for appreciating the nuances of philosophical terminology and its role in shaping philosophical discourse.